Visual skill and pole vaulting - Risk, B. (2000)
This is a very slightly edited version of an article published in the Winter 2000 edition of Track Coach. The main contents are: - INTEGRATION OF SYSTEMS - VISUAL NEEDS OF POLE VAULTING - TRACKING AND FUSION - VISION TESTING AND TRAINING - VISION TESTS FOR ATHLETES - FIELD DETECTION OF VISUAL PROBLEMS - Visual Needs Assessment for the Pole Vaulter.